Ambiguity aversion and incompleteness of financial markets - Mukerji, S; Tallon, J (University of Oxford, 2000)
It is widely thought that incomes risks can be shared by trading in financial assets. But financial assets typically carry some risk idiosyncratic to them, hence, disposing incomes risk using financial assets will involve buying into the inherent idiosyncratic risk. However, standard theory argues that diversification would reduce the inconvenience of idiosyncratic risk to arbitrarily low levels. This argument is less robust than what standard theory leads us to believe: ambiguity aversion can exacerbate the tension between the two kinds of risk to the point that classes of agents may not want to trade some financial assets. Thus, theoretically , the effect of ambiguity aversion on financial markets is to make the risk sharing opportunities offered by financial markets less complete than it would be otherwise.